Guia de portugal (FCG)
Vol.I: Generalidades, Lisboa e arredores. - 3ª reimp. 1991. - 696, [1] p. - Vol. II: Estremadura, Alentejo, Algarve. - 2ª reimp. 1991. - 697, [2] p. - Vol. III: tomo I. - Beira, Beira Litoral. - 3ª ed. - 1993. - 624, [1] p. - Vol. III: tomo II. - Beira, Beira Baixa e Beira Alta. - 2ª reimp. 1994. - 626-996 p. - Vol. IV: tomo I. - Entre Douro e Minho, Douro Litoral, [s.d.]. - 704 p. - Vol. IV: tomo II. - Entre Douro e Minho, Minho. - 3ª ed. - 706-1331p. - Vol. V: tomo I. - Trás-os-Montes e Alto Douro, Vila Real, Chaves e Barroso. - 3ª ed. - 1995. - 534, [1] p. - Vol. V: tomo II. - Trás-os-Montes e Alto Douro, Lamego, Bragança e Miranda. - 4ª ed. - 2015. - [516-1086] p.